PERAN ASAM HUMAT DAN FULVAT DARI KOMPOS DALAM DETOKSIFIKASI ALUMINIUM PADA TANAH MASAM - Imam Wahyudi (BUANA SAINS, 2007)
A study that was aimed to elucidate roles of Gliricidia sepium and Tithonia diversifolia composts and their extracted humic and fulvic acids on aluminum concentration in an Ultisol was conducted in a laboratory. Those composts and humic and fulvic acids extracted from them were mixed with soil and incubated for 90 days. Results of the study showed that the highest decrease in exchangeable Al concentration (90,5%) was observed for Tithonia fulvic acid treatment during 90 days, followed by Tithonia compost (88,4%), Gliricidia fulcic acid (82,3%), Gliricida compost (82,2%), Gliricidia humic acid (82,3%), and Tithonia humic acid (75,7%) treatments. In general, rate of change in exchangeable concentration was fast for the first 45 days, but it then slowed down during the second 45 days (45-90 days). This was particularly observed for humic and fulvic acid treatments, whereas compost treatment still showed subsequent decrease. It was concluded that roles of humic and fulvic acid in reducing exchangeable Al was only a short term, whereas compost played roles in a long term. In terms of capability in reducing exchangeable Al, Tithonia compost and its humic and fulvic acids was better than Gliricidia compost and its humic and fulvic acids